The Role of The Bank Indonesia Bengkulu Library Based on Social Inclusion Through The Children's Reading Corner Program in The Mosque - Azahra, Nanda Aprilia; Samosir, Fransiska Timoria; Sa'diyah, Lailatus (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2024)
This study investigates the role of Bank Indonesia Library Bengkulu in supporting social inclusion through the Children's Reading Corner Program in mosques. The program's initiative came about in response to the need to create inclusive spaces in mosques, going beyond their traditional concept as places of worship. This study aims to analyze the role of the Bank Indonesia Library in Bengkulu in supporting the implementation of the Children's Reading Corner Program in the Mosque in supporting social inclusion in Bengkulu and provide recommendations based on the results of the analysis for further improvement and development. This study used qualitative method with observation, interviews, and ducumentation. The study involved interviews with the Head of Library, Coach, Librarians, and Mosque Administrators who received children's reading corners. The results show that the Bank Indonesia Library Bengkulu is effective in its role, bringing a positive impact on children's participation in the mosque. The Children's Reading Corner program not only improves literacy, but also builds a strong social network. Meanwhile, synergy with stakeholders and internal processes, such as the procurement of reading materials and continuous evaluation need to be improved, because they are key factors for the success of the program.